Influence of varying potassium levels on yield, water productivity, profitability and resource-use efficiency in kharif mungbean (Vigna radiata) under semi-arid conditions of Afghanistan - HAMDULLAH HAMIM; ANIL K CHOUDHARY (The Indian Journal of Agricultural Sciences, 2019)
The application of K2O @ 80 kg/ha could be used as blanket recommendation for obtaining higher productivity, profitability as well as higher resource-use efficiency in kharif mungbean. As a site-specific precision recommendation, the economic optimum K2O dose for kharif mungbean variety NM-94 was worked-out about 76.9 kg K2O/ha which has great promises in saving the potassium fertilizer dose besides enhancing kharif mungbean productivity, profitability and resource-use efficiency under semi-arid conditions of Afghanistan.